2014
DOI: 10.15230/scsk.2014.40.4.373
|View full text |Cite
|
Sign up to set email alerts
|

A Preferred Skin Color by Korean Female in the Age between 30s~40s

Abstract: Abstract:The skin is an organ that covers the outside of the human body. And it regulates body temperature, performs sensory function, deliveries the drug, and represents the abnormality of the internal organs. For these reasons, people have been expressing the condition of the body based on the state of the skin of the face to detect sign of health, "you look well", "face with vitality". Depending on the degree of aging and the environment, it is a fact that skin color, skin texture, moisture and firmness cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…One limitation of this study was that only the L* values were used to divide subjects into the three skin color groups. In a previous study on color preference among Korean women, b* values affected certain color preferences among 180 subjects ranging in age from their 30s to 40s (Kang et al 2014). Although skin color is somewhat difficult to define simply using L* values, there are hundreds of unique skin colors if a* and b* values are included.…”
Section: Discussionmentioning
confidence: 99%
“…One limitation of this study was that only the L* values were used to divide subjects into the three skin color groups. In a previous study on color preference among Korean women, b* values affected certain color preferences among 180 subjects ranging in age from their 30s to 40s (Kang et al 2014). Although skin color is somewhat difficult to define simply using L* values, there are hundreds of unique skin colors if a* and b* values are included.…”
Section: Discussionmentioning
confidence: 99%
“…High transparency is one of the properties of beautiful and ideal skin, according to Korean women . Korean women prefer blue to red in skin color; less yellow color skin looks more transparent and bright at same brightness . Therefore, transparent‐looking skin is one of the goals of a facial makeup product.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to sun exposure, ethnic differences also affect skin tone. From measuring the skin colour of 100 Korean women between the ages of 30 and 40, it was found that the mean skin colour values were as follows: lightness (L*)=63.00, redness (a*) =13.11, and yellowness (b*) =18.70 [15]. But different from the average skin colour of 426 Thais aged between 20-40 years with an average of L*=59.30, a*=9.70 and b*=17.90 and 202 Chinese people aged between 20-40 years who The mean skin colour was L*=58.50, a*=9.80 and b*=15.40 [14].…”
Section: Skin Undertonementioning
confidence: 99%